Identifying Risk Factors of Speech and Language Delay on Children - Muyassaroh, Muyassaroh; Fahrizal, Fahrizal; Naftali, Zulfikar; Yunika, Kanthi; Farokah, Farokah; Widodo, Pujo; Ruspita, Dian Ayu (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Speech and language delay are usually found in various disorders such as mental retardation, hearing impairment, psychosocial, autism, receptive aphasia and cerebral palsy and speech organ disorders. Retrospective research at Dr. Kariadi Hospital found that children aged 13 months to 60 months with complaints of speech problems that were subjected to an objective audiometric examination showed that 79.1% had hearing loss. This research aims to determine the relationship of risk factors with speech and language delays in children. This research was conducted in April 2020 using the cross-sectional with suspicion of late speaking who were examined by Brain evoked response audiometry (BERA) at Dr Kariadi Hospital Semarang. Researchers assessed the delay with the Languange evaluation Scale Trivandum (LEST) questionnaire. Researchers analyzed the data with chi-square test, fisher’s exact. The sample was 80 patients with the mean age was 22.35 months. Mostly in men (67.5%). The most common risk factor was hearing impairment. Hearing impairmentwas associated with speech and language delay. Economic status and bilingual were not associated with speech and language delay in children.